2015
DOI: 10.1136/bjophthalmol-2015-307341
|View full text |Cite
|
Sign up to set email alerts
|

Individualised risk assessment for diabetic retinopathy and optimisation of screening intervals: a scientific approach to reducing healthcare costs

Abstract: ObjectiveTo validate a mathematical algorithm that calculates risk of diabetic retinopathy progression in a diabetic population with UK staging (R0–3; M1) of diabetic retinopathy. To establish the utility of the algorithm to reduce screening frequency in this cohort, while maintaining safety standards.Research design and methodsThe cohort of 9690 diabetic individuals in England, followed for 2 years. The algorithms calculated individual risk for development of preproliferative retinopathy (R2), active prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 12 publications
0
71
0
1
Order By: Relevance
“…Extensive work has been done in the area [3740] of extended screening intervals for those at low risk. The UK National Screening Committee agreed at their committee on 19 November 2015 and published their recommendation in January 2016 that:

For people with diabetes at low risk of sight loss, the interval between screening tests should change from 1 to 2 years.

The current 1 -year interval should remain unchanged for the remaining people at high risk of sight loss.

…”
Section: Programme Resultsmentioning
confidence: 99%
“…Extensive work has been done in the area [3740] of extended screening intervals for those at low risk. The UK National Screening Committee agreed at their committee on 19 November 2015 and published their recommendation in January 2016 that:

For people with diabetes at low risk of sight loss, the interval between screening tests should change from 1 to 2 years.

The current 1 -year interval should remain unchanged for the remaining people at high risk of sight loss.

…”
Section: Programme Resultsmentioning
confidence: 99%
“…It has been demonstrated that in comparison with fixed screening intervals, flexible and individualized screening intervals can be used to extend the screening intervals almost three times (Mehlsen et al 2012) and reduce the number of screening episodes by 40% (Aspelund et al 2011;Lund et al 2016). These benefits are in particular based upon an extended screening interval of more than 12 months in patients with no or minimal DR (Kristinsson et al 1995;Hansson-Lundblad et al 1997;Olafsdottir & Stefansson 2007;Misra et al 2009;Agardh & Tababat-Khani 2011;Echouffo-Tcheugui et al 2013;Taylor-Phillips et al 2016).…”
Section: Use Of Flexible and Individualized Screening Intervalsmentioning
confidence: 99%
“…Biennial screening showed long safety record in Iceland and Sweden [42, 43]. Moreover, adopting biennial screening approach, a reduction in approximately 25% of screening costs can be obtained without increased risk to the patient [44].…”
Section: Telemedicine Screening Programs In Italymentioning
confidence: 99%